Financial behaviour among the Malay community during COVID-19's movement control order (MCO) / Abd Hadi Mustaffa and Nur Balqishanis Zainal Abidin - Mustaffa, Abd Hadi; Zainal Abidin, Nur Balqishanis (Universiti Teknologi MARA, 2022)
Malaysia is no exception when it comes to the COVID-19's global pandemic. Due to COVID-19's rising active and death cases, the Government imposed the movement control order (MCO) as a preventive measure. As a result, most Malaysians were suffering from financial constraints such as income loss and deficit in cash flow, even though the Government proposed several financial aids and initiatives. This study examined the possible factors that influence financial behaviour among the Malay community during MCO, which underpinned under the theory of planned behaviour (TPB). The data collection method employed in this study was a convenience sampling technique collected from 384 Malay respondents through an online survey. Those data were analysed using structural equation modelling- partial least square (SEM-PLS) with 5000 Bootstrapped samples. Based on a twotailed test at 0.01 significance level, the findings indicated that perceived behavioural control and financial knowledge were significantly influenced financial behaviour among the Malay community during MCO. However, financial attitude and subjective norm were resulted not significantly influencing financial behaviour. This study embedded significant contribution in two aspects (1) to supports the underpinning theory of planned behaviour (TPB) with the involvement of financial knowledge as a new construct in influencing the financial behaviour (2) to provide the recent research based on the latest phenomenon, which is the COVID-19 pandemic.